One nation under Trump - Gufferson, Jim; Furtney, B.C.; Ruthless Media; Soundview Media Partners ([Chicago, Ill. ] : Ruthless Studios, 2016)
A comprehensive feature documentary that delves into the zeitgeist of the unstoppable Donald Trump revolution, from the ground floor all the way to the pinnacle of the 2016 American political landscape. Take an unflinching look at what may be the most important political figure of the 21st century.
Originally released as a motion picture in 2016.
Editor, Tyler Wood ; music
In English; close-captioned.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed May 5, 2017).
Keywords: Trump, Donald, -- 1946- -- Political and social views; Presidential candidates -- United States; Presidents -- United States -- Election, 2016.; United States -- Politics and government -- 2009-; Presidential candidates -- United States -- Biography; Biographical films; Documentary films; Nonfiction films; Internet videos; Streaming video